The Influence of Organizational Culture and Knowledge Sharing on Employee Performance with Job Satisfaction as an Intervening at PT. XYZ - Hindami, Ghulam Ilmam; Silvianita, Anita; Pradana, Mahir (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT XYZ, a large rayon fibre producing company in Indonesia, is the site of this study. Declining production, caused by a number of internal and external issues, including declining market demand and operational issues, is the basis of this research. The effect of organisational culture and knowledge sharing on employee performance, with job satisfaction as an intermediate variable, is the purpose of this study. This study uses a quantitative method that uses Partial Least Squares-Structural Equation Modeling (PLS-SEM), which is based on data collected from 286 employees of PT XYZ. The results show that job satisfaction is a mediating variable that enhances the influence of organisational culture and knowledge sharing on performance and job satisfaction. In addition, job satisfaction is also shown to be a mediating variable that strengthens the influence of organisational culture and The main result of this study is that improving organisational culture and knowledge sharing practices is essential to increase employee satisfaction. Ultimately, this will lead to an increase in the general performance of PT XYZ employees.